Crushing and densification of rapid prototyping polylactide foam: Meso-structural effect and a statistical constitutive model. (December 2018) - Wang, Shilong; Zheng, Zhijun; Zhu, Changfeng; Ding, Yuanyuan; Yu, Jilin
Highlights: Closed-cell PLA foams are fabricated by an FDM technique of rapid prototyping. Mechanical properties of foams with different meso‑structures are evaluated. Failure strength of foams is found to be dependent on layer deposition strategy. A statistical constitutive model involving the relative density is proposed. This model well captures the features of initial stress drop and three-stage deformation. Abstract: The deformation characteristics and mechanical behavior of closed-cell polylactide (PLA) foams under quasi-static uniaxial compression are investigated. The PLA foam specimens are constructed numerically with 3D Voronoi technique and prepared with fused deposition modeling (FDM). The effects of meso‑structure, layer deposition strategy and relative density on the crushing and densification behaviors of PLA foams are analyzed. The experimental results indicate that PLA foams with regular meso‑structures are more likely to induce local collapse during compression, and those with random meso‑structures show good performances, such as high specific energy absorption, low stress fluctuation and stable deformation process. The experimental results further reveal that random PLA foams with the deposition layers perpendicular to the loading direction have higher strength and smaller lateral expansion than those with other orientations. The quasi-static compression stress-strain curves of random PLA foams exhibit three typical stages, namely linear elastic stage, plastic collapse stage and densification stage. A stress drop after reaching the initial peak stress is observed. To characterize these features, we propose a statistical constitutive model which takes into account the meso‑structural characteristics and deformation mechanism at the cell scale. This constitutive model contains six parameters and fits the experimental results very well. In particular, it can capture the peak stress at the onset of plastic collapse and the subsequent stress drop of cellular materials. Finally, the dependence of the six parameters in the constitutive model on the relative density is analyzed and the corresponding quantitative statistical relationships are determined.